PERANCANGAN SISTEM INFORMASI ADMINISTRASI KELURAHAN PADA KELURAHAN PASAR BARU KOTA TANGERANG - Santoso, Hari; Putra, Heru Soetanto; Pratama, Aditya (Infotech: Journal of Technology Information, 2019)
The development of information from time to time continues to increase` this is supported by the development of more advanced and adequate technology so that information can be accessed quickly and precisely. Based on the 2014-2018 Pasar Baru Kelurahan Vision that has been established and efforts to support the achievement of the Tangerang City mission by optimizing the authority of information technology-based public services through improving the quality of population administration and civil registration services. In fact in the process of storing data from the results of each work unit is still storing files in the ordner so it takes a long time to find the file that will be needed. To overcome the problems that occur, the authors make the design of a new village market administration information system The system will be built using the PHP programming language and Microsoft Access database. This application can simplify and speed up section heads and employees in accessing their documents independently so that administrative services become more effective and efficient and provide convenience in the processing of urban operational data in data storage services.